Методы реализации проективных преобразований в компьютерной графике - Качанов, Петр Алексеевич; Зуев, Андрей Александрович; Яценко, Константин Николаевич (НТУ "ХПИ", 2016)
В статье рассматриваются методы и алгоритмы реализации проективных преобразований на графических ускорителях. Проводится разделение методов на два семейства: проецирование с одним и с несколькими центрами проекций. Сделан обзор и сравнение методов каждого семейства. Большое внимание уделяется методам с одним центром проецирования. Проводится оценка относительно возможности реализации и применения методов в системах реального времени.

The article discusses methods and algorithms for the implementation of projective transformations on the graphics accelerators. The separation methods into two families: the projection of a single and multiple centers of projections is provided. A review and comparison of methods for each family is made. Much attention is paid to the methods of a single center of projection. It assesses the feasibility and application of real-time systems. The methods on the basis of environment maps are considered. A realization of visual effects on the graphic accelerators as a result of post-processing is proposed. Finally it is concluded that the post-processing method comply with requirements of real-time visualization systems.
Implementation methods of projective transformations in computer graphics
Keywords: графические ускорители; системы визуализации; системы реального времени; graphics accelerators; environment mapping; visualization systems; real-time systems